2013
DOI: 10.1016/j.jamcollsurg.2013.07.242
|View full text |Cite
|
Sign up to set email alerts
|

The cost of major surgery in the sarcopenic patient

Abstract: Background-Sarcopenia is associated with poor outcomes after major surgery. There are currently no data regarding the financial implications of providing care for these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Low muscle mass was associated with adverse LTx outcomes in six of the eleven studies. This is consistent with other major surgical procedures and transplant populations, including liver and renal transplant, that have highlighted adverse postoperative outcomes with low muscle mass [34–37]. This can be partly explained by the fact that low muscle mass represents a state of catabolism with diminished physiological reserve, which is important in order to combat critical illness and infection [38,39].…”
Section: Discussionsupporting
confidence: 82%
“…Low muscle mass was associated with adverse LTx outcomes in six of the eleven studies. This is consistent with other major surgical procedures and transplant populations, including liver and renal transplant, that have highlighted adverse postoperative outcomes with low muscle mass [34–37]. This can be partly explained by the fact that low muscle mass represents a state of catabolism with diminished physiological reserve, which is important in order to combat critical illness and infection [38,39].…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that regular exercise prevents frailty and improves skeletal muscle mass and physical function in older patients, but further studies are needed to assess the effects of preoperative training on muscle mass and survival. In general, modulating skeletal muscle mass seems possible and may therefore represent a promising strategy towards improving postoperative outcomes and even lowering health care costs …”
Section: Discussionmentioning
confidence: 99%
“…In patients with cirrhosis, low skeletal muscle mass is associated with increased mortality on the liver transplantation waiting list and post‐transplant morbidity and mortality, independently of well‐established predictors such as the MELD score . Sarcopenia has also been associated with higher healthcare costs in abdominal cancer patients undergoing surgery . To date, only one study from the United States described the association between gait speed, as a measure of frailty, and increased hospital costs in patients with cirrhosis .…”
Section: Introductionmentioning
confidence: 99%